Cardioprotection by selective SGLT2 inhibitors in a non-diabetic mouse model of myocardial ischemia/reperfusion injury: a class or a drug effect?. (3rd October 2022) - Nikolaou, P E; Mylonas, N; Makridakis, M; Makrecka-Kuka, M; Iliou, A; Zerikiotis, S; Efentakis, P; Kostomitsopoulos, N; Vilskersts, R; Zuurbier, C; Latosinska, A; Vlahou, A; et al.
Abstract: Background: Empagliflozin (EMPA), Dapagliflozin (DAPA) and Ertugliflozin (ERTU) are selective sodium glucose co-transporter 2 inhibitors (SGLT2i) acting against type 2 diabetes mellitus. Purpose: Due to differences in clinical trial outcomes, we aimed to 1) compare the cardioprotective effects of selective SGLT2i in terms of infarct size (IS) reduction and 2) reveal the mechanism of cardioprotection in non-diabetic mice. Methods: C57BL/6 mice were randomized and orally received EMPA (10mg/kg/day), DAPA (9.0mg/kg/day), ERTU (9.7mg/kg/day) or vehicle for 7 days. IS was measured after 30' ischemia (I), and 120' reperfusion (R). EMPA, DAPA and ERTU were given at equivalent stoichiometrically doses (ESD). Body weight and fasting blood glucose (FBG) levels were determined at baseline and at the end of the treatment. On the 7th day, mice were housed in metabolic cages for 24 hours. Urine volume (UV), food and water uptake and 24h-glucose levels were determined to examine the extend of SGLT-2 inhibition by the drugs. In a second series, the ischemic myocardium was taken (10'R), shotgun proteomics were performed and several cardioprotective pathways were evaluated. In a third series, the dominant pathways were evaluated through molecular analyses and mitochondrial functionality. The causal relationships in the mechanism of protection, was established by inhibiting the concomitant cardioprotective pathways. Static, the specific STAT-3 inhibitor and wortmannin (a PI3K inhibitor) were administered and IS was measured upon 30'I/120' R. Results: EMPA and DAPA but not ERTU reduced IS at this dose. Body weight and FBG levels were not affected by the treatments. EMPA, DAPA and ERTU lead to significant increase in UV and urinary glucose levels compared to the control group independently of the water and food intake. There was no significant difference in the parameters among the different SGLT-2i indicating that the chosen doses are sufficient to produce the same pharmacological SGLT-2 inhibition in mice. Proteomics revealed mitochondrial metabolism and NF-kB signaling as significant. Only EMPA preserved mitochondrial functionality in complex I & II linked oxidative phosphorylation. NF-kB, RISK and STAT-3 activation and the downstream reduction in apoptosis were evident in EMPA and DAPA groups coinciding with IS reduction. Static and wortmannin significantly attenuated IS reduction both in EMPA and DAPA groups indicating that STAT-3 and PI3K activation are the leading mechanisms of cardioprotection. Among several upstream mediators, fibroblast growth factor 2 (FGF-2) and caveolin-3 were increased in EMPA and DAPA groups. Conclusions: Short term EMPA, DAPA and ERTU at the chosen ESD inhibit SGLT-2i in a similar extent but only EMPA and DAPA reduce IS. Our study reveals drug specific effects on cardioprotection against I/R injury. Cardioprotection afforded by EMPA and DAPA are STAT-3 and PI3K dependent and associated with increased FGF-2 and Cav-3 expression. Funding Acknowledgement: Type of funding sources: None.